Pemanfaatan Karbon Aktif Tempurung Kelapa Sebagai Adsorben Untuk Penyimpanan Biogas Dengan Variasi Daya Aktivasi - Bismadiatmika Darma, I Nyoman Aditya; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract The world's dependence on dwindling fossil fuels is driving the search for clean and sustainable energy alternatives. Biogas, produced from various types of biomass, offers great potential as an alternative energy source. However, the main challenge in its utilization is biogas storage which requires large volumes and efficient technology. This study aims to analyze the efficiency of biogas storage using Adsorbed Natural Gas (ANG) technology with activated carbon produced from coconut shells. Activated carbon is produced through a microwave activation process with a power variation of 700 to 900 watts with an activation time of 20 minutes, to increase the storage capacity of biogas. The stored biogas can be an alternative energy source. It was shown that by using 900 watts of activation power, the most optimal amount of biogas was produced and used, as seen from the largest reduction in storage mass when released. The results showed that activated carbon activated at 900 watts had the highest biogas storage capacity. Thus, activated carbon from coconut shell has potential as an effective adsorbent for biogas storage. Keywords: Biogas, Activated carbon, Activation power, Biogas storage, Microwave activation.